Size Effect on the Rheological Shear Mechanical Behaviors of Different Joints: A Numerical Study - Kefeng Zhou; Changxin Liu; Su Li; Yanhui Cheng (Geofluids)
Under the condition of constant external stress, the displacement and stress of the joint will be adjusted continuously with time, resulting in the creep phenomenon, that is, the continuous increase of the strain with time, which further causes the damage of the jointed rock mass. In order to study the size effect of joint shear rheological mechanical properties, this paper conducted shear rheological numerical simulations on nonpenetrating and penetrating joint models established in Particle Flow Code (PFC) and analyzed the effect of specimen size on the rheological and shear mechanical behavior of the model. The results show the following: (1) For the rheological direct shear test, the instantaneous shear displacement of the joint increases continuously as the size increases, showing a significant positive size effect. (2) For through-type joints, only the cohesion shows a certain size effect, and the shear strength and friction angle have a nonobvious relation with specimen size. (3) For anchored through-type joints, the increase of the model size leads to a decrease in shear strength, while the friction angle-size effect of joints is not remarkable.